Framing Brand Image Cafe Talenta Menggunakan Q-Ris Sebagai Digitalisasi Keuangan - Thahery, Rusyaidi; Andari, Olfi Janida; Setiawati, Mutiara; Nastiti, Rofi Rimaya; Vanisa, Yola Cesar (Dedikasi: Jurnal Pengabdian Pendidikan dan Teknologi Masyarakat, 2024)
One of the businesses in people's lives with a great desire to form MSMEs, besides that MSMEs are also a form of business that is a source of innovation and creativity. As well as narrating that MSMEs are introduced to the public or known as framing branding.  However, Talenta Cafe still uses cash or non-electronic payment methods because the payment system is still considered less than optimal. Before this Community Service activity was carried out, a situation analysis was carried out which examined the problems of MSME partners, namely implementing the use of QRIS digital applications that were not optimal. The approach taken as well as the PKM implementation method is socialisation or providing knowledge, understanding, and practice, how to optimise the use of E-payment or electronic payment systems using QRIS. Talenta Cafe is located on Jalan Kasah No.45 Pekanbaru. So it can be concluded that the application of e-payment using QRIS at Talenta Cafe is still not running because Talenta Cafe still uses a cash payment system. So that the payment system can be more developed and updated with the development of digitalisation, the community service team helps to implement QRIS In the application of digitalisation technology for MSMEs, there has long been one of them cashless transactions commonly referred to as E-Payment. E-Payment or digitalisation itself has become an innovation in the business world.